2022
DOI: 10.1097/pgp.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Serous Tubal Intraepithelial Carcinoma in a Risk-reducing Salpingo-oophorectomy Specimen From a RAD51D Mutation Carrier: A Case Report

Abstract: The RAD51D gene codes a protein-paralog of the RAD51 DNA recombinase, which catalyzes DNA strand exchange during homologous recombination. Similar to BRCA1/BRCA2, mutations in RAD51D both predispose to ovarian carcinoma and impart sensitivity to poly (ADP-ribose) polymerase inhibitors in preclinical studies. Based on cancer risk prediction models, RAD51D mutations pose a moderate-to-high risk for ovarian cancer warranting consideration for risk-reducing surgery. We report a case of serous tubal intraepithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a recent prospective observational study, the largest single institution series including 27 non BRCA gene mutation carriers, Rush et al [ 40 ] reported a diagnosis of STIC in a carrier of a PALB2 mutation with a strong family history of both BC and EOC; another case report by Gregory-Davis et al [ 45 ] reported a diagnosis of STIC in a RAD51D mutation carrier; HGSC and a low grade serous carcinoma were reported by Schoolmeester et al [ 46 ] in two patients, carrying mutations in RAD51C and CHEK 2, respectively. All these results must be taken with caution, because these mutations have a very low incidence, and large case-control studies are needed to validate the findings; however, we still cannot exclude the possibility of these genes conferring a moderate risk of developing EOC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective observational study, the largest single institution series including 27 non BRCA gene mutation carriers, Rush et al [ 40 ] reported a diagnosis of STIC in a carrier of a PALB2 mutation with a strong family history of both BC and EOC; another case report by Gregory-Davis et al [ 45 ] reported a diagnosis of STIC in a RAD51D mutation carrier; HGSC and a low grade serous carcinoma were reported by Schoolmeester et al [ 46 ] in two patients, carrying mutations in RAD51C and CHEK 2, respectively. All these results must be taken with caution, because these mutations have a very low incidence, and large case-control studies are needed to validate the findings; however, we still cannot exclude the possibility of these genes conferring a moderate risk of developing EOC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%